Pseudo‐Prospective Forecasting of Induced and Natural Seismicity in the Hengill Geothermal Field - Ritz, Vanille; id_orcid:0 000-0002-8773-7608; Mizrahi, Leila; Clasen Repollés, Victor; id_orcid:0 009-0005-6863-1225; Rinaldi, Antonio Pio; id_orcid:0 000-0001-7052-8618; Hjörleifsdóttir, Vala; Wiemer, Stefan; id_orcid:0 000-0002-4919-3283 (American Geophysical Union, 2024)
The Hengill geothermal field, located in southwest Iceland, is host to the Hellisheiði power plant, with its 40+ production wells and 17 reinjection wells. Located in a tectonically active area, the field experiences both natural and induced seismicity linked to the power plant operations. To better manage the risk posed by this seismicity, the development of robust and informative forecasting models is paramount. In this study, we compare the forecasting performance of a model developed for fluid-induced seismicity (the Seismogenic Index model) and a class of well-established statistical models (Epidemic-Type Aftershock Sequence). The pseudo-prospective experiment is set up with 14 months of initial calibration and daily forecasts for a year. In the timeframe of this experiment, a dense broadband network was in place in Hengill, allowing us to rely on a high quality relocated seismic catalog. The seismicity in the geothermal field is characterized by four main clusters, associated with the two reinjection areas, one production area, and an area with surface geothermal manifestations but where no operations are taking place. We show that the models are generally well suited to forecast induced seismicity, despite some limitations, and that a hybrid ETAS model accounting for fluid forcing has some potential in complex regions with natural and fluid-induced seismicity. ISSN:2169-9313 ISSN:0148-0227 ISSN:2169-9356